Answer:
Explanation:
Simplifying
7x + -2y = 1
Solving
7x + -2y = 1
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '2y' to each side of the equation.
7x + -2y + 2y = 1 + 2y
Combine like terms: -2y + 2y = 0
7x + 0 = 1 + 2y
7x = 1 + 2y
Divide each side by '7'.
x = 0.1428571429 + 0.2857142857y
Simplifying
x = 0.1428571429 + 0.2857142857y
///////////////////////
Simplifying
2y = x + -1
Reorder the terms:
2y = -1 + x
Solving
2y = -1 + x
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Divide each side by '2'.
y = -0.5 + 0.5x
Simplifying
y = -0.5 + 0.5x